MSME Strategies to Compete in E-Commerce in Indonesia - Dita Rosyalita; Icha Elyanida (Indonesian Journal of Research and Service Studies, 2024)
This study examines the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in adopting e-commerce and digital marketing strategies. Despite their critical role in the economy, many MSMEs struggle to adapt to digital tools due to barriers such as limited digital literacy, financial constraints, and inadequate infrastructure. The research aims to explore effective strategies for MSMEs to compete in e-commerce, using a library-based methodology that analyzes secondary data from books, journals, and reports. Findings reveal that MSMEs that successfully implement digital marketing tools experience improved visibility, sales, and customer engagement. However, financial and educational barriers remain significant. The study concludes that government support, increased digital literacy, and affordable digital solutions are essential for MSMEs to harness the potential of e-commerce and drive sustainable growth in the digital economy.